2017
DOI: 10.1186/s12931-017-0537-6
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 and ABCG2 drug transporters are differentially expressed in non-small cell lung cancers (NSCLC) and expression is modified by cisplatin treatment via altered Wnt signaling

Abstract: Background: Lung cancer (LC) is still the most common cause of cancer related deaths worldwide. Non-small cell lung cancer (NSCLC) accounts for 85% of all LC cases but is not a single entity. It is now accepted that, apart from the characteristic driver mutations, the unique molecular signatures of adeno-(AC) and squamous cell carcinomas (SCC), the two most common NSCLC subtypes should be taken into consideration for their management. Therapeutic interventions, however, frequently lead to chemotherapy resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 50 publications
1
54
0
1
Order By: Relevance
“…It is crucial to understand the occurrence of chemoresistance, and eventually how to prevent it for combatting cancer effectively [8,27,28], and it is well known that the ABC transporter family are implicated in multidrug resistance and high-expressed levels of ABCG2 have a greater capacity to expel therapeutic drugs [25,29,30]. Furthermore, accumulating ndings reveal that aberrant Wnt/β-catenin signaling and increased ABCG2 expression are closely correlated to multidrug resistance in many cancers [14,15,31], including NPC [18,17]. Also, ABCG2 was reported as a downstream gene of β-catenin since its seven functional transcription factor binding sites have been identi ed in the ABCG2 gene promoter [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to understand the occurrence of chemoresistance, and eventually how to prevent it for combatting cancer effectively [8,27,28], and it is well known that the ABC transporter family are implicated in multidrug resistance and high-expressed levels of ABCG2 have a greater capacity to expel therapeutic drugs [25,29,30]. Furthermore, accumulating ndings reveal that aberrant Wnt/β-catenin signaling and increased ABCG2 expression are closely correlated to multidrug resistance in many cancers [14,15,31], including NPC [18,17]. Also, ABCG2 was reported as a downstream gene of β-catenin since its seven functional transcription factor binding sites have been identi ed in the ABCG2 gene promoter [16].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that the Wnt/β-catenin signaling is closely correlated to DPP resistance in several human tumors [10,11,12]. Moreover, abnormal Wnt/β-catenin signaling activation contributes to upregulation of drug e ux ABC transporters in many cancer types [13,14,15,16], including NPC [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is one of the most commonly used chemotherapies in gynecologic oncology. Unfortunately, many cancers initially respond well to platinum treatment but often develop resistance when tumors recur . Until now, studies have shown that increased DNA repair, altered cellular accumulation, and increased drug inactivation are the main reasons for cells to acquire drug resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear IGF1R specifically binds to and functions as a transcriptional activator of its own promoter, and interferes with signaling pathways (98). Specifically, nuclear IGF1R interferes with Wnt signaling, which upregulates ABC drug transporters and modulates drug responses (99). Regarding the tumor microenvironment, activating IGF1R results in stabilizing hypoxia-inducible factor (HIF)-1α and HIF-2α, and the upregulation of vascular endothelial growth factor (100).…”
Section: Interacting With Ecmmentioning
confidence: 99%